Peran Asbabun Nuzul Qur’an Surah Ali Imran Ayat 159 Dalam Metode Pembelajaran Bagi Mahasiswa/i Pendidikan Bahasa Arab Stambuk 2020 - Ahmad Razali Sinaga; Dedi Masri; Muhammad Alfiansyah; Khairunnisa Khairunnisa; Ayu Vika Lestari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Because the revelation of a verse of the Qur'an can be learned from it. Likewise with asbabun nuzul and the events contained in Q.S Ali-Imran verse 159 that can be learned from it in the form of deliberation learning methods. In this day and age there are many learning methods that are born. The deliberation method can be used for learning methods that will be used by students. This study aims to determine the role of asbabun nuzul Q.S Ali-Imran verse 159 in the learning method which will be used by Arabic language education students later. This study used a descriptive-based qualitative method and interviewed students with Arabic language education in 2020. Based on the results of the study, it was found that asbabun nuzul Q.S Ali-Imran verse 159 served as a learning method for students in Arabic language education in 2020.